EXPERIMENTAL STUDY OF SHEAR BEHAVIOR OF REINFORCED CONCRETE BEAM-COLUMN JOINTS - Ihsanul Amal; Rendy Thamrin; Ruddy Kurniawan (RADJA PUBLIKA, 2026)
Beam-column joints must be designed to be sufficiently strong and capable of withstanding shear forces (horizontal) and factored vertical forces resulting from theiformation of plastic hinges at the beam ends when seismic forces act. The use of stirrups as reinforcement between columns and beams aims to ensure effective force transfer and prevent cracking or structural damage. However, in practice, several challenges are often encountered that may hinder the implementation process. This study employs an experimental method, where direct testing of specimens is conducted to analyze their behavior. The experimental results, including cracking, load, and Deformation, are analyzed to obtain values for strength, ductility, energyidissipation, and joint capacity. Based on the test results, specimen BJ-2 demonstrated a 51.30% increase in capacity compared to specimen BJ-1. However, in terms of ductility, BJ-1 had a higher average value of 3.59, while BJ-2 had a value of 2.8. Regarding energy dissipation, BJ-1 had a lower value of 0.12831 compared to BJ-2, which reached 0.15069. Both specimens experienced initial cracking, first yielding, and ultimate conditions. Additionally, the joint capacity of specimen BJ-2 was 1.7 times greater than that of specimen BJ-1.